Aspecto geoquímicos do material particulado da pluma estuarina do rio Amazonas: fatores que controlam as interações com as águas oceânicas - PEREIRA, Simone Baía (Universidade Federal do Pará, 2023)
The geochemical aspects addressed in this investigation are the determination of the chemical composition of the material in suspension in coastal waters under the influence of the mouth of the Amazon River, indicating the possible location of the source of suspended material, as well as the influences that it suffers along the continent transition -ocean. X-ray diffraction analysis indicated the predominance of kaolinite, illite and quartz clay minerals over the other identified inorganic components, observing the presence of chlorite, sometimes as a subordinate mineral in some samples, sometimes as a trace, and smectite in trace grades, which, like chlorite, is also present as a subordinate mineral. The centesimal mineralogical composition of the particulate material was estimated, associating the analytical results with X-ray diffraction data, using stoichiometric calculation, based on the scientific literature. The results obtained through the stoichiometric calculation confirm the tendency shown by the diffractograms. It is observed that the dominant clay minerals are kaolinite (maximum in 51.19%), associated with high levels of aluminum, distinguishing the dominance of this clay mineral in the sample in which this fact occurs, and illite (maximum in 42.43%) associated At high levels of potassium, when this clay mineral dominates the samples, the presence of iron and titanium colloids was also admitted. The content and nature of the organic matter associated with suspended sediments were evaluated, using elemental analysis for carbon, nitrogen and hydrogen, thermogram records and absorption spectra in the infrared region. In the sediments, organic compounds predominate (clay minerals, silica, iron colloids), with organic matter always having a content below 3.6%. Therefore, in interpreting the records of absorption spectra in the infrared region, the most intense bands are related to the dominant clay minerals in the material, that is, the illite and kaolinite mixture. Bands related to chemical bonds in clay minerals dominate in the infrared spectra. The clear and intense vibration band of the Si-O stretching, which extends from 1200 to 1000 cm-1, with its most significant developments around 1180 and 1034 cm-1, is well representative of structures of the illite and kaolinite types. And there is still a clear band, with weak folds around 950 to 915 cm-1, related to the Al-OH bond; bands around 790-800, 750-780, 640-690 cm-1; or in the range of 400 - 600 cm-1, the intense absorption bands recorded in the range of 4000 - 3400 cm-1, with their various developments, related to the bonds with hydroxyl, –OH, so common in clay minerals and an intense and average band recorded around 1640 cm-1 corresponding to the angular deformation of the HOH bond, a characteristic of constitutive water present in clay minerals. The infrared absorption spectra of humic and fulvic acids from different sources are similar but not identical. The (subtle) differences are the result of brief changes in their compositions. Perhaps the most interesting feature of the spectrum of humic acids is the appearance of intense and broad absorption bands related to the stretching vibrations of the C=O bond of several organic functional groups (carboxylic acids and their derivatives, aldehydes, ketones), in the range from 1709 to 1715 cm-1 and vibrations of aromatic compounds around 1600 to 1613 cm-1. The bands recorded around 1698 to 1701 cm-1 and around 1400 cm-1 indicate the presence of carboxyl and carbonyl groups. The most interesting aspects of the recorded spectra concern the appearance of clear (but weak) absorption bands in the range of 2959-2885 cm-1, attributed to methylene groups –CH2- of hydrocarbons; and the presence of a weak (but clear) band around 1385 cm-1 referring to the carboxyl and/or carbonyl groups. Leading to the conclusion that it is humic material present in organic matter from leaching and drainage of typical Amazonian soils, such as podzolic and latosolic. Elementary organic carbon contents range from 1.27% to 2.05%, while nitrogen contents range from 0.03% to 0.13%. These contents produce high C/N ratios (minimum 12.7% and maximum 68.3%) of material rich in cellulose decomposition products of vegetable origin. The integration of data from the chemical analysis of suspended matter with physical-chemical parameters of coastal waters and the variation in phosphorus levels (minimum of 0.06% to maximum of 0.71%, expressed in P2O5), associated with salinity variation (minimum of 24.31‰ and maximum of 39.19‰), used as limiting parameters, defined the existence of three characteristic zones of origin of suspended material: one predominantly terrigenous, one transitional and one predominantly oceanic biogenic.